Religion and sustainable development in Africa: neo-Pentecostal economies in perspective : (research article) - Golo, Ben-Willie Kwaku (Religion & development, 2022)
The secular approach to development has treated religion as anti-developmental. However, the history of how development was part of missionary activity, such as the provision of health and educational infrastructure in some African countries, has been widely acknowledged. In this paper, therefore, we contend that the marginalisation of religion in development discourse is a result of a faulty and fractured understanding of religion. We argue that sustainable development, if attainable in contemporary Africa, would require that organised and institutional religions in Africa as well as their religious cosmologies, convictions and orientations feature and remain integral to such processes. With reference to neo-Pentecostal economies in Africa, we intend to discuss why and how religion – religious cosmologies, ontologies and institutions – is indispensable in the sustainable development process in Africa. Specifically, keeping in focus the human dimensions of development, we intend to argue that the beliefs, teachings and activities of neo-Pentecostal churches on human salvation, progress and/or transformation, such as prosperity and wealth creation, which has seen them emerge on the socioeconomic scene, indicate the potentials of neo-Pentecostals in particular, and religion in general, to contribute immensely to sustainable development. This, however, is not to gloss over some of the challenges they potentially pose to sustainable development.